Targeting Mitochondria as Therapeutic Strategy for Metabolic Disorders - Sorriento, Daniela (Hindawi Publishing Corporation, 2014)
Mitochondria are critical regulator of cell metabolism; thus, mitochondrial dysfunction is associated with many metabolic disorders. Defects in oxidative phosphorylation, ROS production, or mtDNA mutations are the main causes of mitochondrial dysfunction in many pathological conditions such as IR/diabetes, metabolic syndrome, cardiovascular diseases, and cancer. Thus, targeting mitochondria has been proposed as therapeutic approach for these conditions, leading to the development of small molecules to be tested in the clinical scenario. Here we discuss therapeutic interventions to treat mitochondrial dysfunction associated with two major metabolic disorders, metabolic syndrome, and cancer. Finally, novel mechanisms of regulation of mitochondrial function are discussed, which open new scenarios for mitochondria targeting.